A conceptual study on the use of a regenerator in a hybrid energy storage unit (LIQHYSMES). Issue 1 (November 2015) - Brighenti, F; Ramalingam, R; Neumann, H
Abstract: Wind and photovoltaic parks raise the issue of a discontinuous electrical generation. As an energy carrier with high volumetric energy density, liquid hydrogen is an inevitable choice for large-scale energy storage. But, since balancing loads or rapidly evolving fluctuations on the grid with just hydrogen is unrealistic due to its slow response, it is necessary to integrate it with an electrical energy storage device that enables rapid response. This approach combines the use of a liquefaction plant for hydrogen, and a superconducting magnetic energy storage (SMES). Besides, in this case, conventional liquefaction methods are not a viable solution, meaning that a substantial simplification of the process is possible where a regenerator/recuperator is employed and only if temporary/intermediate storage is required. A study is conducted to develop a regenerator (among other parts) for a proof of concept small scale LIQHYSMES system. A 1D model of differential equations is implemented to investigate the regenerator performances, addressing parameters such as regenerator configuration, material and fluid properties, temperature profiles, etc. Results are then analysed and discussed.